Musculoskeletal manifestations in post-acute sequelae of SARS-CoV-2 infection: a systematic review and meta-analysis - Verma, Amogh; Naidu, Sushma V.; Sulthana, Huma; Ullah, Aftab; Shabil, Muhammed; Sah, Ranjana; Mehta, Rachana; Jan, Asif; Ain, Nur Ul; Rahim, Abdur; Abu Nahla, Ursula (Frontiers in Public Health, 2025)
BackgroundThe COVID-19 pandemic has highlighted a spectrum of long-term sequelae, with musculoskeletal symptoms being a substantial component of Post-Acute Sequelae of SARS-CoV-2 infection (PASC). This systematic review and meta-analysis aimed to evaluate the incidence and nature of musculoskeletal manifestations in individuals recovering from COVID-19.MethodsA systematic search across PubMed, Embase, and Web of Science was performed up to February 15, 2024, to identify studies reporting on musculoskeletal symptoms post-COVID-19. Observational studies which reported any musculoskeletal symptoms of PASC were included. Data were pooled using a random-effects model to calculate the incidence of symptoms, with subgroup analyses based on time since infection. Statistical analysis were conducted in R software (V 4.3).ResultsSixty-four studies were included, demonstrating a pooled prevalence of muscle pain at 28% (95% CI: 22%−35%), which increased to 25.9% (95% CI: 20.7%−31.7%) at 12 months post-infection. Joint pain showed a pooled prevalence of 14.8% (95% CI: 10.6%−20.2%), with no significant temporal change. Muscle weakness was observed in 12.9% (95% CI: 4.2%−32.9%) of patients. Notable heterogeneity was observed across studies (I2 > 89% for all symptoms).ConclusionMusculoskeletal symptoms are prevalent in individuals with PASC, with muscle pain being the most common. The findings highlight the need for comprehensive clinical management and continuous research to create targeted treatments and revise care protocols as the pandemic evolves.